The Image of the Flâneur and its New Vision in Patrick Modianoʼs Novel “In the Cafe of Lost Youth” - Kizim, Nataliia (Studia Philologica, 2025)
This study examines the portrayal of the flâneur in Patrick Modiano’s «In the Café of Lost Youth», exploring how Modiano reimagines this established trope within a contemporary Parisian landscape. The analysis will delve into the specific attributes of the flâneur figure in P. Modiano’s novel, comparing it with three established types within the modern canon: the flâneur-writer, the flâneur-detective and the flâneur-marginal. Also, the nuances of the feminine manifestation of the flâneur image in the novel are investigated. Further, the study examines how P. Modiano redefines the flâneurʼs role in a more contemporary manner influenced by mid-20th-century French psychogeography. The study demonstrates how «drift», a new practice of city perception, affects the flâneurʼs experience and illuminates the complex relationship between the flâneur of the 19th century, the modern city and the newly evolved version of the city walker.